Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Terbaik dengan Metode Simple Additive Waighting (SAW) - Ferdiansyah Laia; Fricles A Sianturi (STMIK Budi Darma, 2021)
Decision support systems have several methods for solving a problem, one of which is the Simple Additive Weighting (SAW) method. The results of this system are only used in the case of a decision support system for employee performance appraisal and cannot be used in other companies because the decision making process at the company has different ways. This system can be used as a tool to determine the feasibility of assessing employee performance at PT. Gamma Enginnering. The system built is web-based using PHP with MySQL database.